Micromechanical Study of Cyclically Loaded Sands with x-ray Microtomography and Digital Image Correlation. (2016) - Salvatore, Erminio; Andò, Edward; Modoni, Giuseppe; Viggiani, Gioacchino
Abstract: The response of granular soil upon cyclic loading and its many practical implications have been the subject of several past experimental and theoretical studies. However, the visual observation of samples reveals a complex pattern of inhomogeneous deformation that rises doubts on the classical phenomenological interpretation of laboratory tests. Aiming to understand the mechanisms activated by alternated compression and extension, a microscale analysis is herein performed. Small samples of dry Hostun sand subjected to cyclic tests are periodically scanned with x-ray tomograph during cyclic triaxial tests and the three-dimensional images are processed with the continuum Digital Image Correlation technique. The evolution of the strain field reveals yielding mechanisms activated during compression and extension with the activation, deactivation and reactivation of shear surfaces localized in different position of the sample and oriented along different directions.